2001
DOI: 10.1002/1521-4141(2001010)31:10<3006::aid-immu3006>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Activation through CD40 ligation induces functional Fas ligand expression by Langerhans cells

Abstract: Langerhans cells (LC) are professional antigen‐presenting cells of dendritic cell (DC) lineage and are critical for the induction of primary immune responses in skin. Following antigenic stimulation, LC migrate to regional lymph nodes and induce antigen‐specific activation of T cells. After primary expansion, the majority of T cells undergo Fas/Fas ligand (FasL)‐mediated apoptotic cell death, thereby suppressing their excessive expansion. Although recent investigations have indicated an immunoregulatory functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…In these earlier studies, many and diverse mechanisms of action were suggested, including immune-specific tolerance through the induction of T-regulatory cells, IL-10 secretion, and IL-2 inhibition 3,9,12,37 ; nonspecific inhibition through the NO system 10,38-40 ; inhibition via indoleamine 2,3-dioxygenase 37,41 ; and apoptosis through death receptors including Fas, TRAIL, and TNF. [13][14][15]17,39,42,43 Likewise, our results suggest that BM-derived DCs obtained after culturing of whole BM with either GM-CSF (supplemental Figure 4) or FLT3 ligand 44 (supplemental Figure 5) do not exhibit detectable levels of perforin or appreciable killing of cognate 2C CD8 T cells. Therefore, our results suggest that the perforin ϩ imDCs grown in our study from purified HSCs represent a novel subpopulation found in a small percentage in the spleen under steady state, which nevertheless can expand in the spleen after GM-CSF administration in vivo.…”
Section: Discussionmentioning
confidence: 73%
“…In these earlier studies, many and diverse mechanisms of action were suggested, including immune-specific tolerance through the induction of T-regulatory cells, IL-10 secretion, and IL-2 inhibition 3,9,12,37 ; nonspecific inhibition through the NO system 10,38-40 ; inhibition via indoleamine 2,3-dioxygenase 37,41 ; and apoptosis through death receptors including Fas, TRAIL, and TNF. [13][14][15]17,39,42,43 Likewise, our results suggest that BM-derived DCs obtained after culturing of whole BM with either GM-CSF (supplemental Figure 4) or FLT3 ligand 44 (supplemental Figure 5) do not exhibit detectable levels of perforin or appreciable killing of cognate 2C CD8 T cells. Therefore, our results suggest that the perforin ϩ imDCs grown in our study from purified HSCs represent a novel subpopulation found in a small percentage in the spleen under steady state, which nevertheless can expand in the spleen after GM-CSF administration in vivo.…”
Section: Discussionmentioning
confidence: 73%
“…Interestingly, FasL-expressing regulatory diffDC did not express CD8a (data not shown). It was reported that Langerhans cells could express FasL and induce apoptosis of Jurkat cells after activation through CD40 ligation (43). Bone marrow DC grown in GM-CSF and IL-4 could express FasL and also induce Jurkat T cell apoptosis in a Fas-dependent pathway in vitro (39).…”
Section: Ifn-g From Activated Cd4 T Cells Induces No Production By Rementioning
confidence: 99%
“…For instance, in mice, epidermal Langerhans cells are known to upregulate their cell-surface expression of FasL after activation with CD40 ligand, resulting in their ability to kill Jurkat cells via apoptosis. 5 We were unable to identify any published reports of tumor killing induced by conventional myeloid DC (mDC;…”
Section: Subsets Of Natural and Induced Kdcmentioning
confidence: 99%